2016
DOI: 10.1007/s11999-015-4512-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation for Teaching Orthopaedic Residents in a Competency-based Curriculum: Do the Benefits Justify the Increased Costs?

Abstract: Background Although simulation-based training is becoming widespread in surgical education and research supports its use, one major limitation is cost. Until now, little has been published on the costs of simulation in residency training. At the University of Toronto, a novel competency-based curriculum in orthopaedic surgery has been implemented for training selected residents, which makes extensive use of simulation. Despite the benefits of this intensive approach to simulation, there is a need to consider i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 19 publications
0
42
0
1
Order By: Relevance
“…Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost. In human surgery, training courses that use mainly simulators are included in the orthopedic surgeon curriculum of some faculties . A recent study provided evidence that a standardized 4‐day arthroscopy training curriculum could objectively improve basic arthroscopy proficiency .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost. In human surgery, training courses that use mainly simulators are included in the orthopedic surgeon curriculum of some faculties . A recent study provided evidence that a standardized 4‐day arthroscopy training curriculum could objectively improve basic arthroscopy proficiency .…”
Section: Discussionmentioning
confidence: 99%
“…In human surgery, training courses that use mainly simulators are included in the orthopedic surgeon curriculum of some faculties. 42 A recent study provided evidence that a standardized 4-day arthroscopy training curriculum could objectively improve basic arthroscopy proficiency. 22 Similar intensive training courses at an early stage may be considered as a part of a more structured veterinary surgical training program.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown, however, that programs that invest heavily in training, simulation, supervision, and frequent feedback can shorten the training process. 11,28 The 'ad-hoc entrustment decisions', even if they happen often, are determined by more factors than one might think at first sight. Clinical supervisors may not always be aware of these factors but may unconsciously measure them.…”
Section: Entrustment Decisionsmentioning
confidence: 99%
“…Importantly, they have noted that to support such a competency-based teaching program, residency programs need to improve the quality of assessment and improve on current formative and summative feedback to their trainees. 25,60,61 These observations have led to the development of a modular, competency-based curriculum that has been implemented in orthopedic surgery. 3,25 This curriculum is structured in a manner similar to our Matrix Curriculum and could be used in a similar competency-based manner once implemented.…”
Section: Neurosurgical Curriculummentioning
confidence: 99%